2018
DOI: 10.1016/j.jchf.2018.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Deficits and Related Brain Lesions in Patients With Chronic Heart Failure

Abstract: HF patients exhibit cognitive deficits in the domains of attention and memory. MTA but not white matter lesion load seems to be related to cognitive impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(100 citation statements)
references
References 24 publications
4
93
1
2
Order By: Relevance
“…Also in our study we found significant relations between ACE-R Fluency and Log-BNP and other interesting associations between 6MWT and both ACE-R Memory subtest and psychomotor speed (Fig 1). This link between the distance covered on the 6MWT, which decreases with age, could reflect the influence that a CHF condition can exert on attention, memory and motor efficiency of CHF patients, synthesizing a general cognitive-motor slowing [12,38]. This hypothesis finds further support in our regression model, where Log-BNP and psychomotor speed independently predicted distance covered at the 6MWT.…”
Section: N(%)supporting
confidence: 64%
See 1 more Smart Citation
“…Also in our study we found significant relations between ACE-R Fluency and Log-BNP and other interesting associations between 6MWT and both ACE-R Memory subtest and psychomotor speed (Fig 1). This link between the distance covered on the 6MWT, which decreases with age, could reflect the influence that a CHF condition can exert on attention, memory and motor efficiency of CHF patients, synthesizing a general cognitive-motor slowing [12,38]. This hypothesis finds further support in our regression model, where Log-BNP and psychomotor speed independently predicted distance covered at the 6MWT.…”
Section: N(%)supporting
confidence: 64%
“…In fact, affective and emotional dysregulation are common in preclinical and prodromal dementia syndromes, often revealing in advance neurodegenerative changes and a progressive cognitive decline [ 35 ]. Other relations frequently described in literature can be found between cognitive impairment and clinical variables [ 36 ] between psychological/neuropsychological factors and clinical variables [ 13 ] or between psychological/neuropsychological factors and functional variables [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in neuronal structure, loss of synapses, and dysfunction of neuronal networks are physiological processes associated with normal aging [23]. In HF patients, the occurrence of CI has often been viewed as coincidental events, because the prevalence of both HF and CI increases with age [4,10,4347].…”
Section: Discussionmentioning
confidence: 99%
“…Recent data have shown that HF and depression may not share common brain involvement and may have specific cognitive deficits. 67…”
Section: Figurementioning
confidence: 99%
“…fatigue). 67 Different questionnaires have been validated for the screening of clinically significant depressive symptoms 68 ( Table 2). In clinical practice, the Patient Health Questionnaire-2 (PHQ-2) is a simple and effective tool for the screening of depressive symptoms that evaluates depressed mood and anhedonia on a six-point scale.…”
Section: Diagnosismentioning
confidence: 99%